1940
DOI: 10.1210/endo-27-5-707
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Metabolism of Crystalline Progesterone

Abstract: MONTREAL, CANADÃ\r N 1938 (1) a preliminary report was made on a study of the metabolism of in' II jected crystalline progesterone, which definitely established sodium pregnandiol -1L glucuronidate as an end product in the metabolism of this compound in the hu' man organism. These experiments have been elaborated and are now being reported in detail.Since this work was published Stover and Pratt (2) reported failure to demon' strate any sodium pregnandiol glucuronidate in the urine of women following injec' ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

1941
1941
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Two years later Ethel Venning and J.S.L. Browne [17] at Montreal discovered the metabolic change of progesterone to pregnanediol by the human organism prior to its excretion in the urine -a discovery which placed a progesterone assay in the hands of the clinicians, who were by this time confirming in their patients much that had been seen in experimental animals.…”
mentioning
confidence: 99%
“…Two years later Ethel Venning and J.S.L. Browne [17] at Montreal discovered the metabolic change of progesterone to pregnanediol by the human organism prior to its excretion in the urine -a discovery which placed a progesterone assay in the hands of the clinicians, who were by this time confirming in their patients much that had been seen in experimental animals.…”
mentioning
confidence: 99%
“…Since these two observations were made, many attempts have been under¬ taken to establish a connexion between them. At first it was thought that the endometrium was essential to the conversion of progesterone to pregnanediol [Venning & Browne, 1937;Hamblen, Powell & Cuyler, 1939]. This was disproved when it was shown that hysterectomized women and normal men could excrete pregnanediol after the administration of progesterone [Buxton & Westphal, 1939;Venning & Browne, 1940].…”
mentioning
confidence: 99%
“…At first it was thought that the endometrium was essential to the conversion of progesterone to pregnanediol [Venning & Browne, 1937;Hamblen, Powell & Cuyler, 1939]. This was disproved when it was shown that hysterectomized women and normal men could excrete pregnanediol after the administration of progesterone [Buxton & Westphal, 1939;Venning & Browne, 1940]. Venning & Browne [1940] then produced evidence to show that in the presence of secretory endometrium or placenta the percentage of administered progesterone excreted as urinary pregnanediol was increased.…”
mentioning
confidence: 99%
See 2 more Smart Citations